Coincidence of Anterior Communicating Artery Aneurysm in a Patient With Carotid Body Tumor: A Case Report - Seddighi, Afsoun; Behrouzian, Sima; Nikouei, Amir; Seddighi, Amir Saied (International Clinical Neuroscience Journal, 2017)
Background: Intracranial aneurysms (IAs) are focal pathologic dilation of cerebral vasculature, which mostly affect the anterior circulation of brain. Carotid body tumors (CBTs) are the most common head and neck parasympathetic paragangliomas. These slow growing neoplasms may cause hypertension along with catecholamine release symptoms, mostly in patients in their fourth decade. This is the second reported case of simultaneous presentation of CBT and IA in a male patient. Case Presentation: A 54-year-old male with positive history of hypertension presented with isolated acute weakness of right upper extremity. Bilateral Doppler ultrasound of carotid arteries showed a mass at left carotid bifurcation, which was confirmed by vessels computed tomography (CT) – angiography. CT scan also demonstrated anterior communicating artery (A-Com) aneurysm. Digital subtraction angiography (DSA) confirmed a right sided A-com artery aneurysm. Aneurismal repair was performed prior to CBT removal. Conclusion: Although multifactorial etiologies, such as hypertension, atherosclerosis and congenital predisposition with vascular abnormalities exists; this case raises the possibility of etiologic relationship between hypertension and hypertensive crises due to catecholamine release and aneurismal development and rupture. Avoidance of possible life threatening complications of aneurismal rupture necessitates preoperative evaluation for CBT in patients with established diagnosis of IA.